What's New in Pediatric Orthopaedic Health Care Disparities?. Issue 9 (11th October 2022) - Arant, Kaetlyn R.; Modest, Jacob M.; Gil, Joseph A.; Cruz, Aristides I.
Abstract : Background: Health care disparities are prevalent within pediatric orthopaedics in the United States. Social determinants of health, such as income, race, social deprivation, place of residence, and parental involvement, all play a role in unequal access to care and disparate outcomes. Although there has been some effort to promote health equity both within pediatric orthopaedics and the US health care system altogether, disparities persist. In this review, we aim to identify major sources of inequality and propose solutions to achieve equitable care in the future. Methods: We searched the PubMed database for papers addressing disparities in pediatric orthopaedics published between 2016 and 2021, yielding 283 papers. Results: A total of 36 papers were selected for review based upon new findings. Insurance status, race, and social deprivation are directly linked to poorer access to care, often resulting in a delay in presentation, time to diagnostic imaging, and surgery. Although these disparities pervade various conditions within pediatric orthopaedics, they have most frequently been described in anterior cruciate ligament/meniscal repairs, tibial spine fractures, adolescent idiopathic scoliosis, and upper extremity conditions. Treatment outcomes also differ based on insurance status and socioeconomic status. Several studies demonstrated longer hospital stays and higher complication rates in Black patients versus White patients. Patients with public insurance were also found to have worse pain and function scores, longer recoveries, and lower post-treatment follow-up rates. These disparate outcomes are, in part, a response to delayed access to care. Conclusions: Greater attention paid to health care disparities over the past several years has enabled progress toward achieving equitable pediatric orthopaedic care. However, delays in access to pediatric orthopaedic care among uninsured/publicly insured, and/or socially deprived individuals remain and consequently, so do differences in post-treatment outcomes. Reducing barriers to care, such as insurance status, transportation and health literacy, and promoting education among patients and parents, could help health care access become more equitable. Level of Evidence: Level IV—narrative review